On long-term stability of an air piston gauge maintained at National Physical Laboratory, India. (June 2020) - Thakur, Vikas N.; Sharma, Rakesh; Kumar, Harish; Omprakash,; Vijayakumar, D.A.; Yadav, Sanjay; Kumar, Ashok
Abstract: The complexity of electronics and hardware in Ultrasonic Interferometer Manometer (UIM) along with a large amount of health and environmental hazardous mercury compelled most of the national metrological institutes (NMIs) to replace UIM with easy to operate and handle based on low-pressure range air piston gauge (APG). Since most of the NMIs have kept APG at the top of traceability chain (only a few have functional UIM), it is an urgent need of time to understand the qualitative change in the effective area at 23 °C ( A e ) of piston-cylinder (p-c) assembly after long-term uses in measurement. The A e of the p-c assembly of APG has been determined using UIM over the years during six in-house comparisons, which are found in the range of 10 ppm in the pressure range 20–120 kPa, which is well within the estimated uncertainties. The quality of p-c assembly was further checked by measuring fall-rate up to the full range of APG, which provides a maximum fall rate of 2.2 mm/min at 350 kPa. The present fall rate is very close to the manufacturer reported value, which suggests long-term stability of p-c assembly after 18 years in the calibration and measurement process. The uncertainties associated with A e have been calculated using the law of propagation of uncertainty and Monte Carlo method and are found to be 9.8 ppm and 9.5 ppm at k  = 2, respectively. The standard deviation of the mean of effective areas is in the range of 10 −10  m 2 to 10 −11  m 2 over 18 years, further, confirm the long-term stability of their consistency in the pressure measurement by p-c assembly. Highlights: APG shows long term stability in zero effective area. The measurement uncertainties are within 12 ppm for the last eighteen years. The zero pressure effective area having a standard deviation of 1.4E-10 m 2 . MCM method validates LPU experimental results. The maximum fall rate of piston obtained was 2.2 mm/min at 350 kPa.